A novel cooperative design with optimized flow field on bipolar plates and hybrid wettability gas diffusion layer for proton exchange membrane unitized regenerative fuel cell. (15th January 2022) - Zhang, Zhonghao; Guo, Mengdi; Yu, Zhonghao; Yao, Siyue; Wang, Jin; Qiu, Diankai; Peng, Linfa
Abstract: Proton exchange membrane unitized regenerative fuel cell (PEM-URFC), as a novel electrochemical device which combines fuel cell (FC) and water electrolyzer (WE), is gradually being recognized as promising power source with reduction of size and cost. Unsatisfying mass transfer ability under the two adverse modes is the main factor hindering the commercialization of URFC, which calls for a bifunctional cell structure. In this study, a novel cooperative design with interdigitated flow field on bipolar plate (BPP) and a hydrophilic-hydrophobic alternative gas diffusion layer (GDL) is proposed to compose a new means of mass transfer under both working modes. Cells made up with different combinations of BPPs and GDLs are tested to confirm the usefulness of the new design. The cell with the optimized structure shows great progress in performance. The current density increases by 11.5% under FC mode and 4.8% under WE mode. EIS test and GDL's structure measurement are also carried out to further explain the working principle of the positive effect made by the new system on the cell. It is also found that the novel design of the URFC in this study has great adaptability to various operating conditions based on the stability test. Graphical abstract: Novel cooperative design with optimized flow field and hybrid wettability gas diffusion layer for FC mode and WE mode of proton exchange membrane unitized regenerative fuel cell. Image 1 Highlights: A cooperative design of flow field and GDL is proposed to improve URFC. Hydrophilic-hydrophobic alternative GDL is fabricated for reversible operating. Current density increases by 11.5% under FC mode and 4.8% under WE mode. EIS test, element characterization and surface structure test are carried out. The novel design has great adaptability to various operating conditions.